INCLUSIVE EDUCATION AS A FACTOR IN THE FORMATION OF A HUMANISTIC EDUCATIONAL ENVIRONMENT IN THE CONTEXT OF DIGITAL TRANSFORMATION - Shohsanam Matupayeva (Modern American Journals, 2025)
The article examines inclusive education as a key factor in shaping a humanistic educational environment in the era of digital transformation. It emphasizes that the integration of inclusive principles into modern educational systems requires not only the adaptation of teaching methods and infrastructure but also the transformation of pedagogical values toward humanism, empathy, and equality. Digital transformation creates new opportunities for inclusive learning through the implementation of assistive technologies, online platforms, and artificial intelligence tools that facilitate access to education for learners with diverse needs. At the same time, it poses challenges related to digital inequality, teacher readiness, and the preservation of the human-centered essence of education. The study highlights the need to prepare educators for inclusive digital pedagogy, focusing on their professional competencies, emotional intelligence, and ability to create a supportive learning atmosphere. The results underline that inclusive education, combined with digital innovation, contributes to the development of an educational environment that respects individual differences, promotes collaboration, and supports lifelong learning.
Keywords: Inclusive education, humanistic environment, digital transformation, teacher competencies, accessibility, educational innovation, empathy, equality, pedagogical values, lifelong learning.